2023
DOI: 10.1002/anie.202217233
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticancer Heterobimetallic PtIV−AuIComplexes Show High In Vivo Activity and Low Toxicity

Abstract: AuI‐carbene and PtIV−AuI‐carbene prodrugs display low to sub‐μM activity against several cancer cell lines and overcome cisplatin (cisPt) resistance. Linking a cisPt‐derived PtIV(phenylbutyrate) complex to a AuI‐phenylimidazolylidene complex 2, yielded the most potent prodrug. While in vivo tests against Lewis Lung Carcinoma showed that the prodrug PtIV(phenylbutyrate)‐AuI‐carbene (7) and the 1 : 1 : 1 co‐administration of cisPt: phenylbutyrate:2 efficiently inhibited tumor growth (≈95 %), much better than 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…[5][6][7][8] These shortcomings have prompted researchers and clinicians to search for more effective strategies. 9 Extensive investigations on the antitumor potential of non-Pt metal complexes of ruthenium (Ru), [10][11][12] iridium (Ir), 13,14 titanium (Ti), 15 gold (Au) [16][17][18] etc., with distinct mechanisms of action than DNA-targeting Pt drugs, have led to the identification of several promising candidates which are in preclinical or advanced clinical trials. 19,20 Alternatively, combination therapy comprising a Pt drug and other drugs with a distinct mechanism of action (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] These shortcomings have prompted researchers and clinicians to search for more effective strategies. 9 Extensive investigations on the antitumor potential of non-Pt metal complexes of ruthenium (Ru), [10][11][12] iridium (Ir), 13,14 titanium (Ti), 15 gold (Au) [16][17][18] etc., with distinct mechanisms of action than DNA-targeting Pt drugs, have led to the identification of several promising candidates which are in preclinical or advanced clinical trials. 19,20 Alternatively, combination therapy comprising a Pt drug and other drugs with a distinct mechanism of action (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, efforts have been made for the development of metallodrugs, a strategy to combine two or more active transition metals in a single platform in order to achieve a synergistic effect of two metals. To date, pioneering studies have been reported to improve the cytotoxicity of Pt­(IV) prodrugs by combining with other metals which include Cu­(II), Fe­(II), , Ru­(II), ,, Re­(I), Gd­(III), , Au­(I), etc. For instance, Zhu and co-workers have reported heterodinuclear Pt­(IV)-Ru­(II) anticancer prodrugs to combat both drug resistance and cancer metastasis. , Gasser and co-workers have demonstrated a multi-targeted Ru­(II)-Pt­(IV) conjugate that combines cancer-activated chemotherapy with photodynamic therapy with multi-action mechanisms to overcome drug-resistant cancers .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhu and co-workers have reported heterodinuclear Pt­(IV)-Ru­(II) anticancer prodrugs to combat both drug resistance and cancer metastasis. , Gasser and co-workers have demonstrated a multi-targeted Ru­(II)-Pt­(IV) conjugate that combines cancer-activated chemotherapy with photodynamic therapy with multi-action mechanisms to overcome drug-resistant cancers . Sessler and Meade groups have illustrated water-soluble, cell-permeable Gd­(III)-Pt­(IV) conjugates as potent antitumor agents that have the simultaneous capability of imaging and chemotherapeutic effect. , In other cases, of late, Gibson and coworkers have developed Pt­(IV)-Au­(I)-carbene prodrugs that displayed efficient in vitro and in vivo anticancer activity and potent inhibitors of thioredoxin reductase, an enzyme which involved in maintaining redox homeostatic and apoptosis . Despite recent advances, the development of heterodinuclear Pt­(IV) with Ir­(III) has been unexplored yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Pt IV compounds containing Ru‐ p ‐cymene [23] and Gd‐texaphyrin [26] fragments resulted very promising in vivo. It is surprising that only one article reports on Pt IV containing Au fragments so far, [27] despite the impressive antitumor properties displayed by gold compounds. Gold(I) compounds such as antirheumatic FDA‐approved Auranofin (Figure 1e) and related compounds have attractive antimigratory, apoptotic, and antiangiogenic properties while causing immunogenic cell death (ICD) [28] .…”
Section: Introductionmentioning
confidence: 99%